Effects of phase offset error for asymmetric communication link in heterogeneous mobile network - Hasan M.K.; Ismail A.F.; Hashim W.; Islam S.; Khairolanuar M.H. (Springer Verlag, 2023)
4G mobile communication systems; Femtocell; Interference suppression; Mobile telecommunication systems; Standards; IEEE 1588; Imperfect coverage; Interference mitigation; Lte- advanced; Model results; Phase offsets; Time synchronization; Timing and synchronization; Wireless telecommunication systems